Vulneración de los artículos 74º y 104º de la Constitución Política del Perú por la aplicación de la ley N.º 30506 - Cruz Rodríguez, Luis Miguel (2023)
The general objective of this research is to analyze| how Articles 74º and 104º of the Constitution of Peru are violated by the application of Law 30506. A qualitative and explanatory design methodology was used, where the sample consisted of legal material and documentary sources (standards, records, resolutions, books, journals, and jurisprudence) around articles 74º and 104º of the Constitution and Law 30506, as well as by 5 lawyers specialized in Tax Law of the city of Trujillo, to whom an interview guide was applied. It is concluded that, Articles 74º and 104º of the Political Constitution of Peru are violated by the application of Law 30506, since the principle of constitutionality is affected, the principle of reservation of the law and the tax power of the State, in view of the fact that both the Constitution, the Rules of Procedure of the Congress and the Organic Law of the Executive Branch have a generic and unlimited form with regard to the delegation of legislative powers to the Executive, which is not exceptional or extraordinary, In addition, the work of parliamentary control implies a posteriori knowledge, which is not really a control mechanism. In addition, it was obtained that no legal arameters are established to regulate the granting of legislative powers to the Executive under Peruvian law.